THE ROLE OF CHAT GPT (GENARATIVE PRE-TRAINED TRANSFORMER) IN PREPARING FINANCIAL DATA FOR FINAL ASSIGNMENTS: STUDY OF ACCOUNTING STUDENTS AT JEMBER UNIVERSITY - Shofyan Hadi (The Asia Pacific Journal Of Management Studies, 2025)
This research aims to explore the potential of Chat GPT in improving the quality of accounting students' work. In the digital era which is characterized by rapid technological developments, AI offers various applications that can support students in the learning process and application of accounting concepts. The research method used was a mixture, including surveys of accounting students at several educational institutions and in-depth interviews with lecturers and industry practitioners. The research results show that the application of Chat GPT, such as data analysis, accounting process automation, and information system development, can increase the efficiency and effectiveness of completing academic tasks. However, this research also identified challenges, including a lack of understanding of Chat GPT technology among students and lecturers, as well as limited access to the necessary tools. These findings provide important insights for the development of accounting curricula that are more relevant and responsive to industry needs, as well as recommend concrete steps for the integration of AI in accounting education. Thus, it is hoped that this research can contribute to increasing the competency of accounting students in the digital era, preparing them to face the challenges and opportunities offered by modern technology.